Association between IGF-I, IGF-IR and GHRH gene polymorphisms and growth and carcass traits in beef cattle - Curi, Rogerio Abdallah [UNESP]; de Oliveira, H. N.; Silveira, Antonio Carlos [UNESP]; Lopes, C. R. (Elsevier B.V., 2005)
Molecular biology techniques are of help in genetic improvement since they permit the identification, mapping and analysis of polymorphisms of genes encoding proteins that act on metabolic pathways involved in economically interesting traits. The somatotrophic axis, which essentially consists of growth hormone releasing hormone (GHRH), growth hormone (GH), insulin-like growth factors I and II (IGF-I and IGF-II), and their associated binding proteins and receptors (GHRHR, GHR, IGF-IR and IGF-IIR), plays a key role in the metabolism and physiology of mammalian growth. The objectives of the present study were to estimate the allele and genotype frequencies of the IGF-I/SnaBI, IGF-IR/TaqI and GHRH/HaeIII gene polymorphisms in different genetic groups of beef cattle and to determine associations between these polymorphisms and growth and carcass traits. For this purpose, genotyping was performed on 79 Nellore animals, 30 Canchim (5/8 Charolais+3/8 Zebu) animals and 275 crossbred cattle originating from the crosses of Simmental (n=30) and Angus (n=245) sires with Nellore females. In the association studies, traits of interest were analyzed using the GLM procedure of SAS and least square means of the genotypes were compared by the Tukey test. Associations of IGF-I/SnaBI genotypes with body weight and subcutaneous backfat were significant (p < 0.05), and nearly significant for longissimus dorsi area (p=0.06), with the 1313 genotype being favorable compared to the AB genotype. No significant associations were observed between this polymorphism and weight gain or carcass yield (P > 0.05). The IGF-IR/TaqI and GHRH/HaeIII polymorphisms showed no association with production traits. (c) 2004 Elsevier B.V All rights reserved.
Keywords: beefcattle; polymorphisms; candidate gene; growth; carcass